From the Seclusion Room to the Space of Revolution: The Intonation of Sisterhood and Women’s Resistance in the Film Kartini - Aprilia, Airin Ina; Ramadanni, Eka Nur; Tsabita, Abelia Nuha; Shofah, Novia Adibatus (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article analyzes gender injustice experienced by female characters in Kartini, a film directed by Hanung Bramantyo, focusing on R.A. Kartini, R.A. Roekmini, and R.A. Kardinah. The study employs a qualitative descriptive approach, grounded in paralinguistic theory (particularly aspects of intonation and vocal expression) and feminist literary criticism. It aims to reveal how intonation in the characters’ dialogues reflects sisterhood and resistance against the patriarchal system. The findings show that phonological expressions such as intonation, pitch, vocal stress, as well as crying and laughter serve as emotional communication tools and symbolic strategies of resistance to gender domination. The seclusion room (pingitan) in the film is not portrayed as a space of isolation, but rather as a place where solidarity grows and strategies for women's struggle against structural injustice are forged.